Gendered geographies : space and place in South Asia - Raju, Saraswati (Oxford University Press, 2011)
The volume interprets the influential early nineteenth century debate on Sati by placing it in the context of a varied tradition of heterogeneous and ambivalent western responses to the rite. By tracing the shifting interpretations of this custom found in European accounts, it demonstrates how changing representations of Indian society and culture were interwoven with socio-ideological trends and concerns in the observer s own society. It illustrates how nineteenth century British fascination with Sati was related to debates on gender, religion, and suicide in the metropolis at the time. The author explores the processes by which cultures seek to understand each other, arguing that colonial knowledge was based much on the recognition of similarity between cultures as on the assertion of a diametric opposition between East and West